Analysis of Physical Environmental Factors Affecting the Incidence of Pulmonary Tuberculosis in Magelang City (Universitas Negeri Semarang, 2021)
Tuberculosis is a disease caused by Mycrobacterium Tuberculosis which is transmitted by Tuberculosis patients with BTA (Basil Tahan Asam) (+), namely TB patients whose sputum microscopic examination found BTA bacteria. Magelang is the region with the highest pulmonary TB cases in Central Java Province for 3 consecutive years. In addition, the discovery of new cases of BTA (+) CNR also occupied the highest place for 3 consecutive years in 2015, 2016 and 2017. Even though in 2017 the number of new case finds of BTA (+) decreased drastically from the previous year, which was 284 per year. 100,000 population, but still ranked 1st CNR new cases of BTA (+).The purpose of this study was to analyze physical environmental factors that influence the incidence of pulmonary tuberculosis in Magelang City.This study used a case control research design. The population consisted of all people who had been tested for pulmonary tuberculosis at the puskesmas. The sample consisted of 100 pulmonary tuberculosis patients and 100 non-pulmonary TB patients taken using purposive sampling technique. The instrument uses a questionnaire sheet, checklist, observation, room thermometer, hygrometer, and meter. Data analysis used Chi-square test and logistic regression test.The results of the analysis show that there is a relationship between lighting (p-value 0.043), humidity (p-value 0.045), room temperature (p-value 0.021) with the incidence of pulmonary tuberculosis. Multivariate analysis showed that room temperature was not ideal, with an OR of 0.321 which had the most influence on the incidence of pulmonary TB.The most dominant physical environmental factor is room temperature which is not ideal. From several related physical environmental factors, it is necessary to provide detailed information regarding pulmonary tuberculosis so as to maintain a clean and healthy environment.